Interrupted-time-series analysis of the impact of COVID-19 pandemic on blood culture utilization in Shanghai - Chenyang Jin; Qun Zhang (BMC Infectious Diseases)
Abstract Background Limited information is available regarding the changes in blood culture utilization following the COVID-19 pandemic. Blood culture utilization rate is a critical indicator of diagnostic efficiency for infectious diseases. This study aims to describe the impact of the COVID-19 pandemic on blood culture utilization rate in Shanghai. Methods We conducted an interrupted time-series analysis based on electronic health records from the Shanghai Changzheng hospital from January 2014 to October 2023. The outcome measure was the rate of blood culture utilization among inpatients with a temperature of ≥ 39.4 °C. The impact of the COVID-19 pandemic on blood culture utilization was quantified by fitting linear segmented regression models and modelling the relative cumulative effect by the end of the study. The pandemic period was defined from February 2020, following the implementation of strict containment measures in Shanghai. Results A total of 23,761 inpatients with a temperature of ≥ 39.4 °C were included in the analysis. From 2014 to 2023, the utilization rate of hospital blood cultures increased initially and then declined, with a significant change point following the onset of the COVID-19 pandemic (Cochran-Armitage trend test, P < 0.001). The COVID-19 pandemic was associated with a significant change in the slope of the blood culture utilization rate (pre-COVID-19 vs. during-COVID-19: 0.31% per month vs. -0.30% per month, P < 0.001), resulting in a relative cumulative effect of -12.55% at the end of the study (95% confidence interval, -19.08 to -6.03). This corresponds to 407 inpatients who did not have blood cultures taken during-pandemic, which represents a significant deviation from pre-pandemic trends. Conclusions The upward trend in blood culture utilization rate among inpatients stalled during the COVID-19 pandemic and did not return to pre-pandemic levels following the pandemic. These findings suggest that the pandemic had a lasting impact on diagnostic practices. More targeted intervention measures are needed to promote appropriate utilization of blood cultures.